Taking stock of the Reintegrative Shaming Experiments (RISE): Understanding challenges and preparing for the future - Scheuerman, Heather (Criminal justice studies, 2025)
The Australian Reintegrative Shaming Experiments (RISE) reflect one of, if not the most, comprehensive examinations of family group conferences (FGC) to date. Various studies have used these data to highlight challenges, obstacles, and unintended consequences of restorative justice (RJ) processes. The purpose of this review is to systematically analyze issues associated with RJ as revealed by RISE that have implications for the implementation of RJ in general. We review how RISE data have been used to empirically evaluate the underlying processes and outcomes of RJ according to justice processes, shaming, and shame management; RJ’s effectiveness in terms of recidivism and reparation; and factors that condition this effectiveness, such as characteristics of offenders, crime type, and gender. We end with a discussion of suggestions for addressing these challenges in the future.